2009
DOI: 10.1080/14756360802188313
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of peroxynitrite treatment on fish liver catalase activity

Abstract: The effect of peroxynitrite (PN), a highly toxic agent, on catalase (CAT) activity in fish liver microsomal homogenates was determined. PN was synthesized by mixing acidic hydrogen peroxide solution with sodium nitrite solution and then adding sodium hydroxide solution into the mixture in order to stabilize the highly labile compound peroxynitrous acid (ONOOH) in peroxynitrite anion form (ONOO 2 ). The effect of PN and decomposed peroxynitrite (DPN), prepared by preincubation with HCl, was monitored by using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Interestingly, this occurred in parallel with the increase in the activity of the CAT enzyme in this group. Studies have already demonstrated that CAT can be inhibited by nitric oxide (NO) and peroxynitrite [45,46], and that CAT itself is also capable of conducting the oxidation of NO and the decomposition of peroxynitrite. A previous study with gastric carcinoma cells demonstrated that inhibition of CAT allowed selective reactivation of the NO/peroxynitrite pathway [47], thus revealing the role of this enzyme in the catabolism of this factor.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this occurred in parallel with the increase in the activity of the CAT enzyme in this group. Studies have already demonstrated that CAT can be inhibited by nitric oxide (NO) and peroxynitrite [45,46], and that CAT itself is also capable of conducting the oxidation of NO and the decomposition of peroxynitrite. A previous study with gastric carcinoma cells demonstrated that inhibition of CAT allowed selective reactivation of the NO/peroxynitrite pathway [47], thus revealing the role of this enzyme in the catabolism of this factor.…”
Section: Discussionmentioning
confidence: 99%